2009
DOI: 10.1038/bmt.2009.39
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for invasive aspergillosis and related mortality in recipients of allogeneic SCT from alternative donors: an analysis of 306 patients

Abstract: Invasive aspergillosis (IA) is a serious complication in patients undergoing allogeneic haematopoietic stem cell transplantation (HSCT), particularly from donors other than HLA-identical sibling. All 306 patients who underwent alternative donor HSCT between 01 January 1999 and 31 December 2006 were studied. Late IA was defined as occurring X40 days after HSCT. The median followup was 284 days (range, 1-2709). Donors were matched unrelated (n ¼ 185), mismatched related (n ¼ 69), mismatched unrelated (n ¼ 35) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 25 publications
(46 reference statements)
6
118
1
3
Order By: Relevance
“…For these reasons, our overall 1-year CI of 11% cannot be compared with other studies reporting late or very-late IFD incidence after alloSCT (ranging from 7 to 10%). [3][4][5]11 Concerning the type and timing of IFD, we found that, as in previous studies, Aspergillus spp. was the most frequent isolate and the lungs were the most common site, 18 and that the CI of IFD increased during the first year with a gradual decline of episodes until 5 years after SCT.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For these reasons, our overall 1-year CI of 11% cannot be compared with other studies reporting late or very-late IFD incidence after alloSCT (ranging from 7 to 10%). [3][4][5]11 Concerning the type and timing of IFD, we found that, as in previous studies, Aspergillus spp. was the most frequent isolate and the lungs were the most common site, 18 and that the CI of IFD increased during the first year with a gradual decline of episodes until 5 years after SCT.…”
Section: Discussionsupporting
confidence: 87%
“…24 Concerning the univariate analysis of prognostic factors, our findings were consistent with other studies showing that corticosteroid dosage, aGVHD, cGVHD and CMV infection could increase the risk of post-engraftment or late IFD. 1,5 In addition, we found that post-engraftment IFD was associated with several risk factors that have been previously related with early or overall IFD, such as older age, delayed neutrophil engraftment, previous SCT, HLA mismatch and non PBSCT. 3,4 Our data suggest that ATG-containing regimens could increase the risk of IFD, which is in line with other studies reporting ex vivo T-cell depletion using Cl of IFD alemtuzumab as a risk factor for IFD.…”
Section: Site Of Infectionmentioning
confidence: 62%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] Based on prior studies, IFI is estimated to occur in 8-17% of pediatric HSCT patients, with a mortality rate of 35-50%. [1][2][3][4][5][6] Incidence varies in the different post-transplant phases, with peaks both pre-and post-engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity and mortality associated with the latter remain high despite recent advances in prevention, diagnosis, and treatment (8,9). Long recognized as critical to host defense against Aspergillus species, particularly when conidia escape macrophage phagocytosis (10), PMNs provide essential anticonidia defense and prevent conidial germination by releasing proteolytic enzymes and rapidly producing ROS in the so-called oxidative burst (11,12).…”
mentioning
confidence: 99%